Functional promoter -308G>A variant in tumor necrosis factor α gene is associated with risk and progression of gastric cancer in a Chinese population. - Yan Hong (Public Library of Science (PLoS), 2013)
Background Tumor necrosis factor-α (TNF-α) plays a crucial role in the development and progression of gastric cancer. A functional polymorphism, -308 G>A (rs1800629), which is located in the promoter of TNFA gene, has been suggested to alter the production of TNF-α and influence cancer risk. In the present study, we sought to investigate whether this polymorphism has effects on the risk and progression of gastric cancer in a Chinese population. Methods We genotyped the TNFA -308 G>A polymorphism using the TaqMan method in a two-stage case-control study comprising a total of 1686 gastric cancer patients and 1895 cancer-free subjects. The logistic regression was used to assess the genetic associations with occurrence and progression of gastric cancer. Results We found a significant association between the variant genotypes and increased risk of gastric cancer [P = 0.034, odds ratio (OR) = 1.39, 95% confidence interval (CI) = 1.01-1.67, GA/AA vs. GG]. Similar results were observed in the follow-up replication study. When combined the data from the two studies, we found a more significant association (P = 0.001, OR = 1.34, 95%CI = 1.13-1.59), especially for older subjects (>65 years). Furthermore, the patients carrying the variant genotypes had a significantly greater prevalence of T4 stage of disease (P = 0.001, OR = 2.19, 95%CI = 1.39-3.47) and distant metastasis (P = 0.013, OR = 1.61, 95%CI = 1.10-2.35). Conclusions Our results suggest that the functional promoter -308 G>A polymorphism in TNFA influence the susceptibility and progression of gastric cancer in the Chinese population.